Energy expenditure during everyday activities – a study comparing people with varying mobility limitations due to multiple sclerosis and healthy controls*. (December 2014) - Coote, Susan; O'Dwyer, Catriona
Abstract Purpose: To investigate energy expenditure of people with multiple sclerosis (MS) during everyday activities. Methods: Fifteen healthy controls, 19 people with MS who used at most a stick to walk outdoors (MS-A), and 11 people with MS who used bilateral support for gait (MS-B) completed scripted everyday activities. A portable indirect calorimetry unit calculated energy expenditure. Steps were counted from video. Results: There was no significant difference in kcal between the three groups (ANOVA: F(2, 42) = 2.877, p = 0.067). There was a significant difference in steps: F(2, 42) = 17.93, p < 0.001. (Controls–MS-A 470.5, 95% CI 85.2, 855.7, Control–MS-B 1091.3, 95% CI 648.5, 1534.1, MS-A–MS-B 620.8, 95% CI 198.2, 1043.4.) Energy cost of movement was estimated by dividing kcal by steps. The Kruskal–Wallis analysis found significant difference for total (x2 = 11.726, df2, p = 0.003), Walking (x2 = 9.01, p = 0.011), Stairs (x2 = 16.436, 2, p < 0.001). Post-hoc analysis revealed significant differences between MS-B group and control and MS-A groups. Conclusions: People with MS do not use more energy than healthy controls during everyday activities at a self-selected pace. People with MS take significantly fewer steps during activities of daily living's. People who use bilateral support for gait have greater energy cost per step for walking and stairs activities. Implications for Rehabilitation This study found that the energy cost of movement is greater for people with MS with significant disability. Energy expenditure is an important consideration when prescribing physical activity and structured exercise for people with disability. It may be more appropriate to have energy, rather than movement, targets when prescribing physical activity for this population.